Pengaruh Suhu dan Tekanan Uap Air terhadap Fiksasi Kayu Kompresi dengan menggunakan Close System Compression Temperature and Steam Pressure Dependency on the Fixation of Compressed Wood by Close System Compression - Yusuf Amin; Wahyu Dwianto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2006)
It is known that compression wood by heat treatment needs approximately 20 hours at 180ºC to attempt the permanent fixation of compressive deformation. On the other hand, even the permanent fixation of compressive deformation by steam treatment is reached in 10 minutes at the same temperature, this method needs expensive apparatus and inapplicable for large wood dimensions. These both problems can be solved by Close System Compression (CSC) method. CSC is a method to press the wood inside an airtight seal chamber, which is placed between the two hot press plates. Wood moisture contents, which evaporate due to heat from hot press, are trapped inside the CSC and produce steam. The wood species used in this research was Randu (Bombax ceiba. L) with dimensions of 2 cm (L) x 2 cm (T) x 3 cm (R). The wood specimens were compressed into 2 cm in radial direction inside the CSC at 140ºC, 160ºC, and 180ºC for 10 min, 20 min and 30 min. They were compressed in air-dried, water saturated and steam saturated conditions, because it was predicted that moisture content of wood and steam pressure, which was produced inside the CSC has significantly effects on the fixation of wood, beside the temperature.The result shows that moisture content of the wood has an effect on the decreasing of recovery of set. However, it was needed 180ºC temperature and 10 kg/cm2 steam pressure to attempt the permanent fixation. Therefore, it was necessary to add water to produce the steam pressure besides that was produced from the evaporation of wood moisture content.